Nonnus of Panopolis in context III old questions and new perspectives - Doroszewski, Filip 1980-; Jażdżewska, Katarzyna ca. 20./21. Jh (Mnemosyne supplements, 2021)
"Nonnus of Panopolis (5th c. AD), the most important Greek poet of Late Antiquity, is best known for his Dionysiaca, a grand epic that gathers together all myths associated with Dionysus, god of wine and mysteries. The poet also authored the Paraphrase of St. John's Gospel which renders the Fourth Gospel into sophisticated hexameter verse. This volume, edited by Filip Doroszewski and Katarzyna Jażdżewska, brings together twenty-six essays by eminent scholars that discuss Nonnus' cultural and literary background, the literary techniques and motifs used by the poet, as well as the composition of the Dionysiaca and the exegetical principles applied in the Paraphrase. As such, the book will significantly deepen our understanding of literary culture and religion in Late Antiquity"--